Clinical Nomogram for Predicting the Prognosis of Patients With Pulmonary Venous Obstruction After Total Anomalous Pulmonary Venous Connection Repair - Chen, Ling; Qiu, Zhihuang; Xu, Fan; Chen, Xingfeng; Chen, Liangwan (Frontiers in Cardiovascular Medicine, 2022)
Background The aim was to establish a nomogram to quantify the risk of postoperative pulmonary venous obstruction (PVO) and to make a scientific decision through the decision curve. Methods 151 PVO patients with TAPVC repair in our hospital from December 2008 to December 2015 were involved in this study. A nomogram was generated based on the contribution weights of variables, which were found out by logistic analysis. The optimal clinical decision point was determined by the decision analysis and clinical impact curve, which could assess the net benefit between the nomogram and each independent risk factor for postoperative pulmonary venous obstruction (PVO). Result PVO with TAPVC repair was found to be positively and independently correlated with preoperative pulmonary hypertension, surgical methods, and preoperative pulmonary venous stenosis. Conclusion(s) The study introduced a novel model to aid in clinical decisions making for the TAPVC patients individually, which may shed light on the evaluation of PVO risk.